2014
DOI: 10.1093/cid/ciu125
|View full text |Cite
|
Sign up to set email alerts
|

NAP1 Strain Type Predicts Outcomes From Clostridium difficile Infection

Abstract: Background Studies conflict regarding the importance of the fluoroquinolone-resistant North American pulsed-field gel electrophoresis type 1 (NAP1) strain in Clostridium difficile infection (CDI) outcome. We describe strain types causing CDI and evaluate their association with patient outcomes. Methods CDI cases were identified from population-based surveillance. Multivariate regression models were used to evaluate the associations of strain type with severe disease (ileus, toxic megacolon, or pseudomembrano… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
108
0
4

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 162 publications
(114 citation statements)
references
References 32 publications
2
108
0
4
Order By: Relevance
“…Initial clinical cure (defined as no diarrhea for 2 consecutive days after completion of standard-of-care antibiotic therapy administered for ≤16 days) was an exploratory end point. Secondary analyses included the rate of recurrent C. difficile infection in the subgroup of participants in the modified intention-to-treat population who had an initial clinical cure, as well as in prespecified subgroups of participants with risk factors for recurrent C. difficile infection or for adverse outcomes related to C. difficile infection: an age of 65 years or older, 20,21 a history of C. difficile infection, 3,4 compromised immunity, 22,23 clinically severe C. difficile infection (defined as a Zar score ≥2; scores range from 1 to 8, with higher scores indicating more severe infection), 24 and infection with a strain associated with poor outcomes (strain 027, 20,25-27 078, 28 or 244 29,30 ). A secondary end point was the rate of sustained cure (i.e., initial clinical cure of the baseline episode of C. difficile infection and no recurrent infection through 12 weeks), also known as global cure or sustained clinical response.…”
Section: Prespecified End Pointsmentioning
confidence: 99%
“…Initial clinical cure (defined as no diarrhea for 2 consecutive days after completion of standard-of-care antibiotic therapy administered for ≤16 days) was an exploratory end point. Secondary analyses included the rate of recurrent C. difficile infection in the subgroup of participants in the modified intention-to-treat population who had an initial clinical cure, as well as in prespecified subgroups of participants with risk factors for recurrent C. difficile infection or for adverse outcomes related to C. difficile infection: an age of 65 years or older, 20,21 a history of C. difficile infection, 3,4 compromised immunity, 22,23 clinically severe C. difficile infection (defined as a Zar score ≥2; scores range from 1 to 8, with higher scores indicating more severe infection), 24 and infection with a strain associated with poor outcomes (strain 027, 20,25-27 078, 28 or 244 29,30 ). A secondary end point was the rate of sustained cure (i.e., initial clinical cure of the baseline episode of C. difficile infection and no recurrent infection through 12 weeks), also known as global cure or sustained clinical response.…”
Section: Prespecified End Pointsmentioning
confidence: 99%
“…2,3 Since the emergence of the hypervirulent NAP1/027 strain in recent years, there has been an increase in the severity of CDI, with more patients failing medical therapy and requiring emergent colectomy. 2,4,5 Recent epidemiologic data suggests that CDI is a growing burden among surgical patients and is associated with increased morbidity, mortality, hospital stay and health care costs. 6,7 The risk of CDI is highest among patients requiring intestinal tract manipulation or reconstruction, a population very similar to patients undergoing radical cystectomy (RC).…”
Section: Introductionmentioning
confidence: 99%
“…Many of these are risk factors for CDI in general, including advanced age, hospitalization, and exposure to fluoroquinolone and cephalosporin antibiotics (18). The data suggesting an association between BI/NAP1/027 and severe CDI in adult patients are conflicting (19). However, differences in study settings, CDI and BI/NAP1/027 prevalences, small study sample sizes, and the specific CDI outcomes assessed likely contribute to the discrepancies among previous studies.…”
Section: Clinical Implications Of CDI Caused By Bi/nap1/027mentioning
confidence: 99%
“…However, differences in study settings, CDI and BI/NAP1/027 prevalences, small study sample sizes, and the specific CDI outcomes assessed likely contribute to the discrepancies among previous studies. A recent U.S. study of patients identified from population-based CDI surveillance in 8 states comprehensively assessed the relationship between strain type and CDI severity (19). In that study of 2,057 CDI cases, after controlling for several confounding variables for CDI severity, BI/NAP1/027 was associated with severe disease (i.e., leukocytosis, ileus, toxic megacolon, or pseudomembranous colitis) (adjusted odds ratio [AOR], 1.74; 95% confidence interval [CI], 1.36 to 2.22), severe outcome (i.e., intensive care unit admission, colectomy for CDI, or death within 30 days of CDI) (AOR, 1.66; 95% CI, 1.09 to 2.54), and death within 14 days (AOR, 2.12; 95% CI, 1.22 to 3.68).…”
Section: Clinical Implications Of CDI Caused By Bi/nap1/027mentioning
confidence: 99%